2005
DOI: 10.1016/j.jmhg.2005.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in men and women

Abstract: Venous thromboembolism (VTE) is a frequent illness with an annual incidence of 0.1 to 0.2%. Over the last decades, a multitude of acquired and inherited risk factor of VTE has been identified. From the circumstantial risk factors, advancing age and male sex are the important ones. Male sex is not only a risk factor for a first episode of VTE but also confers a high risk of recurrence. Diagnostic and therapeutic strategies are not different between men and women. Venous thromboembolism is diagnosed by combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
1
0
1
Order By: Relevance
“…We detected that age>50 was a risk factor for VTE in women; this might contradict data showing that younger women present a higher thrombotic risk [15]; however, other studies found similar frequencies in both sexes, except a two-fold higher rate in men aged>75 [16], and a slightly higher risk of DVT in old women and a lower risk for PE [17]. In our study, men were at a significantly higher risk for PE than women were, concordant with literature [18]. Although literature shows a 2-to 4-fold increase in thrombotic risk of hormonal therapy, we found no association with VTE, mainly due to the low prevalence (1.83% in VTE and 5.07% in women with VTE) and thus, we did not detail the analysis (according to the dose, route of administration) [8].…”
Section: Discussionsupporting
confidence: 67%
“…We detected that age>50 was a risk factor for VTE in women; this might contradict data showing that younger women present a higher thrombotic risk [15]; however, other studies found similar frequencies in both sexes, except a two-fold higher rate in men aged>75 [16], and a slightly higher risk of DVT in old women and a lower risk for PE [17]. In our study, men were at a significantly higher risk for PE than women were, concordant with literature [18]. Although literature shows a 2-to 4-fold increase in thrombotic risk of hormonal therapy, we found no association with VTE, mainly due to the low prevalence (1.83% in VTE and 5.07% in women with VTE) and thus, we did not detail the analysis (according to the dose, route of administration) [8].…”
Section: Discussionsupporting
confidence: 67%
“…A Cox proportional hazards regression model was used to compare risk for VTE between cohorts. As a first step, we adjusted on age only since it is a well-known risk factor for VTE [ 2 , 23 , 27 , 28 ]. As a second step, risk factors and all confounders described above were tested in univariate analysis, and then included in backward selection to select the final fully adjusted regression models.…”
Section: Methodsmentioning
confidence: 99%
“…Определяли частоту ВТЭ в расчете на 1000 пациенто-лет и время до первого события ВТЭ с использованием кривой Kaplan -Meier. Анализ проводили с использованием регрессионной Coxмодели для сравнения риска ВТЭ между когортами, в том числе с учетом фактора возраста, поскольку известно, что он является важным для риска ВТЭ [16,29,39,57,79].…”
Section: проблема номера / Problem Of This Issueunclassified